2020
DOI: 10.1093/humrep/deaa192
|View full text |Cite
|
Sign up to set email alerts
|

Association of polycystic ovary syndrome or anovulatory infertility with offspring psychiatric and mild neurodevelopmental disorders: a Finnish population-based cohort study

Abstract: STUDY QUESTION Is maternal polycystic ovary syndrome (PCOS) associated with increased risks for a broad spectrum of psychiatric and mild neurodevelopmental disorders in offspring? SUMMARY ANSWER Maternal PCOS and/or anovulatory infertility is independently, and jointly with maternal obesity, perinatal problems, cesarean delivery and gestational diabetes, associated with increased risks in offspring for almost all groups of ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 39 publications
3
60
1
3
Order By: Relevance
“…However, this strengthens the findings in the main analysis, as the association is found is not completely attributable to maternal BMI. Similarly, Chen et al 12 found that their results suggested a synergistic effect of PCOS and obesity on offspring anxiety. This agrees with the mouse model experiments where the influence of maternal obesity was explored.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, this strengthens the findings in the main analysis, as the association is found is not completely attributable to maternal BMI. Similarly, Chen et al 12 found that their results suggested a synergistic effect of PCOS and obesity on offspring anxiety. This agrees with the mouse model experiments where the influence of maternal obesity was explored.…”
Section: Discussionmentioning
confidence: 89%
“…This study was conducted in a US population-based birth cohort, where both the PCOS status of the mother and any childhood anxiety diagnosis was reported by the mother when the children 7 or 8 years old. Chen et al 12 used a Finnish population-based cohort study and reported a 33% increased risk (HR 1.33; 95% CI 1.26–1.41) for an anxiety diagnosis in children born to women with PCOS, however they did not find a difference for male and female children. Comparatively, we report a slightly higher risk for anxiety overall, and specifically an increased risk for daughters born to women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, six articles (three cohort studies and three case-control studies) were included in the present meta-analysis. 10,11,[18][19][20][21] Figure 1 presents the process of the included articles.…”
Section: Description Of Studiesmentioning
confidence: 99%
“… 5 The onset of mental retardation is usually in the stage of development, specifically before the age of 18. 6 This distinguishes mental retardation that occurs during development from mental retardation that occurs later in life for a variety of reasons. 7 The incidence of mental retardation generally does not exceed 2%.…”
Section: Introductionmentioning
confidence: 99%